PENINGKATAN KINERJA PERSONIL POLRI BAGIAN SUMBER DAYA MANUSIA DALAM MEMBERIKAN PELAYANAN ADMINISTRASI KEPEGAWAIAN DI POLRES MAGELANG KOTA - Anwar , Muhamad Choirul; Hamid, Muda Setia (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this research is to determine the causes of the performance of the National Police Personnel in the Human Resources Department in Providing Personnel Administration Services at the Magelang City Police Station which is less than optimal and to formulate efforts to improve the performance of the National Police Personnel in the Human Resources Department in Providing Personnel Administration Services at the Magelang City Police Station. The results of the research found that the cause of the low performance of the National Police Personnel in the Human Resources Department in providing personnel administration services at the Magelang City Police is because there are still members who do not have knowledge in the field of HR management, there are still members who do not have the skills in providing administrative services in the field of HR management, there are still members whose work attitude (Attitude) is not good because they do not optimize working hours to complete the work. Efforts made to improve the performance of National Police Personnel in the Human Resources Department in providing personnel administration services at the Magelang City Police are increasing knowledge through (a) formal training carried out through face-to-face learning processes in the classroom, at least through training, seminars, courses and upgrading and (b) non-formal training at least includes guidance in the workplace carried out by the direct superior or a team of experts. Efforts to improve skills by attending training, management seminars, technical guidance in accordance with the task and increasing interaction and activities with other people as an effort to learn by doing. and the efforts made to improve the behavior or attitude of the National Police Personnel in the HR Department at the Magelang City Police are through motivational activities to overcome poor work attitudes (Attitude), such as not optimizing working hours to complete work and avoiding delays in carrying out tasks, so mentoring efforts need to be made. or coaching by direct superiors who then created a standard system regarding performance assessment and providing incentives (reward and punishment), outbound activities and also religious activities carried out at the Magelang City Police Station.